2020
DOI: 10.1177/1535370220941424
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between monocyte chemoattractant protein-1/chemokine (C-C motif) ligand 2 and coronary plaque characteristics

Abstract: In this work, our primary objective was to examine the interrelationship among the serum level of chemokine (C-C motif) ligand 2 (CCL2) and plaque characteristics in coronary culprit lesions. The clinical data of 116 coronary heart disease patients who were hospitalized in the Department of Cardiology of Henan Province People's Hospital from February 2015 to June 2017 were retrospectively analyzed. The study population was subdivided according to the concentration of CCL2 into low CCL2 group and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The results of previous studies are not consistent. In a study by Li et al of patients with CAD, it was found that the MCP-1 concentration was positively correlated with the percentage of fibrous-fatty plaque and necrotic core, the components that form the noncalcified plaque component in our study and negatively correlated with the percentage of fibrous tissue [41]. Different results were obtained by Fuchs et al, who reported that the MCP-1 concentration was correlated with the coronary plaque burden and that higher MCP-1 levels were related to higher calcium content (r = 0.47, p = 0.004), necrotic core (r = 0.38, p = 0.02) and lower content of the fibrous tissue (r = −0.34, p = 0.03) [30].…”
Section: Discussionsupporting
confidence: 66%
“…The results of previous studies are not consistent. In a study by Li et al of patients with CAD, it was found that the MCP-1 concentration was positively correlated with the percentage of fibrous-fatty plaque and necrotic core, the components that form the noncalcified plaque component in our study and negatively correlated with the percentage of fibrous tissue [41]. Different results were obtained by Fuchs et al, who reported that the MCP-1 concentration was correlated with the coronary plaque burden and that higher MCP-1 levels were related to higher calcium content (r = 0.47, p = 0.004), necrotic core (r = 0.38, p = 0.02) and lower content of the fibrous tissue (r = −0.34, p = 0.03) [30].…”
Section: Discussionsupporting
confidence: 66%
“…IL‐6 is a cytokine with pleiotropic activity not only produced by macrophages but also secreted by endothelial cells following stimulation of inflammatory cytokines such as IL‐1 or TNF‐α, and tissue hypoxia (Tanaka, Narazaki, & Kishimoto, 2016). Both MCP‐1 and IL‐6 overexpression have been implicated in several pathologic conditions including atherosclerosis, thrombosis, and inflammatory diseases (Li, Chen, Zhang, Li, & Liu, 2020; Lin et al, 2014; Oikonomou et al, 2020) and, moreover, the serum concentrations of IL‐6 and MCP‐1 in all patients with severe COVID‐19 are significantly elevated compared with those in healthy controls (Kang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“… 31 MCP1 is involved in the genesis, progression, inflammatory response and immune process of CAD, which suggests the potential as a liquid biomarker of CAD. 32 Although meta-analysis revealed that higher circulating MCP-1 levels were associated with higher long-term cardiovascular mortality and increased long-term risk of stroke, its association with CAD risk was still inconsistent and few were conducted in Chinese. 11 , 13 …”
Section: Discussionmentioning
confidence: 99%